Multifarious Trajectories in Plant-Based Ethnoveterinary Knowledge in Northern and Southern Eastern Europe - Mattalia, Giulia; Belichenko, Olga; Kalle, Raivo; Kolosova, Valeria; Kuznetsova, Natalia; Prakofjewa, Julia; Stryamets, Nataliya; Pieroni, Andrea; Volpato, Gabriele; Sõukand, Renata (Frontiers in Veterinary Science, 2021)
Over the last century in the European context, animal production has been transformed by the dynamics of centralization and decentralization due to political and economic factors. These processes have influenced knowledge related to healing and ensuring the welfare of domestic animals. Therefore, our study aimed to document and compare current and past ethnoveterinary practices, and to identify trajectories in ethnoveterinary knowledge in study regions from both northern and southern Eastern Europe. In the summers of 2018 and 2019, we conducted 476 interviews, recording the use of 94 plant taxa, 67 of which were wild and 24 were cultivated. We documented 452 use reports, 24 of which were related to the improvement of the quality or quantity of meat and milk, while the other 428 involved ethnoveterinary practices for treating 10 domestic animal taxa. Cattle were the most mentioned target of ethnoveterinary treatments across all the study areas, representing about 70% of all use reports. Only four plant species were reported in five or more countries (Artemisia absinthium, Hypericum spp., Linum usitatissimum, Quercus robur). The four study regions located in Northern and Southern Eastern Europe did not present similar ethnoveterinary knowledge trajectories. Bukovinian mountain areas appeared to hold a living reservoir of ethnoveterinary knowledge, unlike the other regions. Setomaa (especially Estonian Setomaa) and Dzūkija showed an erosion of ethnoveterinary knowledge with many uses reported in the past but no longer in use. The current richness of ethnoveterinary knowledge reported in Bukovina could have been developed and maintained through its peculiar geographical location in the Carpathian Mountains and fostered by the intrinsic relationship between the mountains and local pastoralists and by its unbroken continuity of management even during the Soviet era. Finally, our results show some patterns common to several countries and to the veterinary medicine promoted during the time of the Soviet Union. However, the Soviet Union and its centralized animal breeding system, resulted in a decline of ethnoveterinary knowledge as highly specialized veterinary doctors worked in almost every village. Future research should the complex networks of sources from where farmers derive their ethnoveterinary knowledge.